2017
DOI: 10.1093/annonc/mdx017
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib benefit inEGFR-mutant NSCLC patients withT790M-mutation detected by circulating tumour DNA

Abstract: ctDNA from liquid biopsy can be used as a surrogate marker for T790M in tumour tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 20 publications
10
134
2
Order By: Relevance
“…A number of generations of inhibitors (e.g., erlotinib, gefitinib, afatinib, and osimertinib) have been developed to target specific EGFR mutations that are frequently found in untreated lung cancer and recurrent lung cancers [4147]. Therefore, lung cancer management is known to benefit from longitudinal sampling, monitoring, and selection of different inhibitors [48]. The fact that EGFR mutations can vary over time further highlights the significance of longitudinal monitoring of multiple plasma samples during the disease progression and post-treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A number of generations of inhibitors (e.g., erlotinib, gefitinib, afatinib, and osimertinib) have been developed to target specific EGFR mutations that are frequently found in untreated lung cancer and recurrent lung cancers [4147]. Therefore, lung cancer management is known to benefit from longitudinal sampling, monitoring, and selection of different inhibitors [48]. The fact that EGFR mutations can vary over time further highlights the significance of longitudinal monitoring of multiple plasma samples during the disease progression and post-treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to tissue biopsy, liquid biopsy, especially ctDNA sequencing, allows comprehensive and longitudinal monitoring of tumour genomics non‐invasively. While the correlation of ctDNA and efficacy of EGFR‐TKI has been extensively investigated, this work presents one of the most comprehensive ctDNA genomic analyses of tumour evolution during osimertinib treatment, which is a third‐generation EGFR‐TKI. The present study demonstrated that ctDNA is an important approach to predict prognosis and monitor response.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, several studies have demonstrated the spatial heterogeneity of T790M. However, either T790M alone or T790M/sensitizing mutation ratio failed to consistently predict the outcome from osimertinib, indicating a complex clinical interpretation for T790M status. Similarly, in our study, T790M existence and clonal status in plasma failed to identify two subgroups with significantly different PFS, although patients who lost detectable T790M during treatment were more likely to develop early resistance and have a shorter PFS.…”
Section: Discussionmentioning
confidence: 99%
“…The study also concluded that given the 30% false negative rate of plasma T790M testing, those with negative plasma T790M still needed a tissue biopsy to accurately determine the T790M status. Another study assessed the efficacy of osimertinib when T790M status was determined in ctDNA in 48 EGFR-mutant NSCLC patients with disease progression (42). The T790M mutation was detected in 50% of patients, with osimertinib achieving a partial response rate of 62.5% and a stable disease rate of 37.5%.…”
Section: Role Of Ctdna In the Resistance Settingmentioning
confidence: 99%